Sistema de controlo distribuído baseado em ethernet - Farinha, Luís Miguel dos Santos (2011)
ABSTRACT: The growing competitiveness among industrial organizations has been increasing the speed at which production processes are changed. Adding to this there is a crescent demand to decrease production costs. In order to respond to these demands distributed control systems have emerged. These, highly flexible and low cost systems, can be made even less expensive if reduced resources microcontrollers are used, or if an existent communication infrastructure, such as Ethernet, is used since these already exist in most organizations. In this thesis an Ethernet based distributed control system is proposed, which is flexible enough to be used in systems with distinct properties. Pole placement adaptive control algorithms are used to control the analyzed application examples. In what is concerned to processing units, the viability of using microcontrollers as computing units, both to run control algorithms and support communications, together with an Ethernet controller, are evaluated.